Long non-coding RNA Hotair promotes gastric cancer progression via miR-217-GPC5 axis - Dong, Xiaolin; He, Xiaoxue; Guan, Aoran; Huang, Weikang; Jia, Hongping; Huang, Yun; Chen, Sijin; Zhang, Zhibo; Gao, Jianpeng; Wang, Hui (Life sciences (1973), 2019)
The oncogenic role of lncRNA Hotair has been acknowledged in subset of malignancies, including gastric cancer (GC). However, the detailed molecular mechanisms that contribute to its oncogenic role of are largely elusive. This study was designed to explore the underlying mechanism that contributes the regulatory role of Hotair in GC pathogenesis and progression. Expression pattern of lncRNAs in GC tissues and adjacent normal tissues were identified by using microarray analysis. The cell proliferation of GC cells was examined by CCK-8 assay and colony formation assay, while migration and invasion capabilities of GC cells were examined by Transwell (with or without Matrigel) assay. Cell apoptosis was examined by Flow cytometer. qRT-PCR and western blotting were used to examine the expression of Hotair, miR-217, and other related genes. The potential target relationships were predicted by miRcode algorithm, and validated by dual luciferase reporter gene assay. We observed that Hotair was frequently up-regulated in GC tissues and cell lines, and high Hotair level was positively correlated with poor prognosis in GC patients. Knockdown of Hotair inhibited GC cells' viability, migration, invasion, Epithelial mesenchymal transition process. MiR-217 was decreased while GCP5 was increased in GC cells. Hotair negatively regulated the expression of miR-217 in GC while miR-217 targeted GCP5 to down-regulate its expression. Hotair promoted GC development by promoting GCP5 expression via sponging miR-217. Hotair could serve as a potentially prognostic indicator and provide new light into its underlying biological-molecular mechanism in GC.